PENGARUH PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN MEDIA ATTENTION SEBAGAI VARIABEL MEDIASI - Fiddyana Lasimpala; Maria Natalia (Universitas Pamulang, 2020)
The objective of this research is to determine the impact of Corporate Social Responsibility Disclosure to firm value with media attention as mediating variable. In this research media attention is proxied with a website, while firm value is measured using the Tobin’s q ratio. The population in this research are manufacturing companies that listed on the Indonesia Stock Exchange in 2016. This research refers to Li et al. (2016) & Putra et al. (2017) research which shows that the performance of Corporate Social Responsibility is positively related to firm value. The difference between this research and previous research is the use of 144 manufacturing companies listed on the Indonesian Stock Exchange in 2016 as a research sample. Corporate Social Responsibility Disclosure measured using performance indicators from the Global Reporting Initiative (GRI) 4.1.Sampling was conducted using a purposive sampling method with criteria the companies that publish information related to Corporate Social Responsibility in the year of 2016 at annual report and at the company's official website. The sample of research that meets the criteria are 87 samples. Type of data used in this research is secondary data that obtained through official www.idx.co.ic. The data were analyzed by using path analysis with the SPSS 20 application. The results showed that the Corporate Social Responsibility Disclosure had an effect on the firm value. Meanwhile, media attention is not able to mediate the influence of Corporate Social Responsibility Disclosure on firm value